Biomarkers associated with cardiovascular disease in women with spontaneous preterm birth: A case–control study - Elin Täufer Cederlöf; Susanne Lager; Anders Larsson; Inger Sundström Poromaa; Bertil Lindahl; Anna‐Karin Wikström; Christina Christersson (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Women with spontaneous preterm birth have an increased risk of cardiovascular disease later in life. Studies suggest potential pathophysiological mechanisms in common, but whether these could be identified by measurement of soluble circulating protein biomarkers in women with spontaneous preterm birth is unknown. The aim of this study was to determine if protein biomarkers associated with cardiovascular disease distinguish women with spontaneous preterm birth from healthy controls, both at pregnancy and at follow up. Material and methods Study participants were identified in the population‐based Uppsala biobank of pregnant women in Sweden, where plasma samples were collected in mid‐pregnancy. In a first screening phase, we identified participants who subsequently experienced spontaneous preterm birth (<37 weeks) in the index pregnancy (N = 13) and controls (N = 6). In these samples, differences in protein expression were examined by comparative mass spectrometry. In a second validation phase, we invited 100 cases with previous spontaneous preterm birth in the index pregnancy and 100 controls (matched for age, body mass index, and year of delivery) from the same source population, to a follow‐up visit 4–15 years after pregnancy. At follow up, we collected plasma samples and data on cardiovascular risk factors. We measured concentrations of selected biomarkers identified in the screening phase, as well as lipid profiles in samples both from pregnancy (biobank) and follow up. ClinicalTrials.gov registration NCT05693285. Results In the screening phase, fibrinogen, cadherin‐5, complement C5, factor XII, plasma kallikrein, apolipoprotein M, and vitamin D‐binding protein differed significantly at pregnancy. In the validation phase, 65 women agreed to participate (35 cases and 30 controls), with a median follow‐up time of 11.8 years since pregnancy. The concentration of fibrinogen (p = 0.02) and triglycerides (p = 0.03) were slightly higher in cases compared with matched controls at follow up. Conclusions Compared with women without preterm birth, those with spontaneous preterm birth had slightly higher concentrations of fibrinogen, both at mid‐pregnancy and a decade after pregnancy. Additionally, we found slightly higher concentration of triglycerides at follow up in women with previous spontaneous preterm birth. The relevance of this finding is uncertain but might indicate potential pathophysiological mechanisms in common between spontaneous preterm birth and cardiovascular disease.